Burnout in primary healthcare providers: A cross-sectional study from Al-Khobar, Saudi Arabia - Banan Almalki; Hani Alshehri; Lateefah Alharbi; Sarah Aldossary; Amira Alshowkan (PLoS ONE, 2026)
Aim Job burnout is one of the emerging challenges in the healthcare sector which caused various issues among the primary healthcare providers. Hence, the present study was designed to evaluate the prevalence of burnout among the healthcare workers working in the primary healthcare clinics situated in the Alkhobar, Eastern Region of Saudi Arabia. Methods The study was also aimed to evaluate the associated factors related to the burnout. This cross-sectional study included 114 healthcare providers working in the different primary health care centers. Maslach Burnout Inventory (MBI) was used to evaluate the burnout among the respondents. Results The other questions were included the demographics and clinical factors. It was found that the prevalence of the burnout was 21.1%. Emotional exhaustion was found significantly high among females compared to males and those who had monthly income less than 12K compared to those with more than 12K monthly income. Daily patient load was another factor causing emotional exhaustion among the respondents. Conclusion In conclusion, the feeling of depersonalization among the participants was found to be very high followed by emotional exhaustion. The identification of the contributing factors would help to reduce the prevalence. Some of those factors were socio-demographic related and some were related to work.